Dogma. Does the conceptual scheme and uninterpreted content dualism make sense? (Diametros, 2007)
The article is a critical analysis of Davidson’s thesis that the idea of conceptual schemes which organize sense data does not make sense. An overview of the arguments presented by Donald Davidson in his essay, “On the very idea of a conceptual scheme”, shows that the notion of alternative interpretative structures cannot in fact be based upon differences in concepts alone. Wherever we would like to speak about different concepts, we can speak only of different convictions. However, Davidson’s theory fails in cases which depend not on conceptual differences, but on the different physiological structures of persons. Such cases cannot be reduced to differences in convictions. The solution to this problem proposed in the present work consists in relativizing truth to the interpretive apparatus of a given person.